Odanacatib treatment affects trabecular and cortical bone in the femur of postmenopausal women: results of a two-year placebo-controlled trial - Engelke, Klaus; Fuerst, Thomas; Dardzinski, Bernard; Kornak, John; Ather, Shabana; Genant, Harry K.; De Papp, Anne (Journal of Bone and Mineral Research, 2015)
Odanacatib, a selective cathepsin K inhibitor, increases areal bone mineral density (aBMD) at the spine and hip of postmenopausal women. To gain additional insight into the effects on trabecular and cortical bone, we analyzed quantitative computed tomography (QCT) data of postmenopausal women treated with odanacatib using Medical Image Analysis Framework (MIAF; Institute of Medical Physics, University of Erlangen, Erlangen, Germany). This international, randomized, double-blind, placebo-controlled, 2-year, phase 3 trial enrolled 214 postmenopausal women (mean age 64 years) with low aBMD. Subjects were randomized to odanacatib 50 mg weekly (ODN) or placebo (PBO); all participants received calcium and vitamin D. Hip QCT scans at 24 months were available for 158 women (ODN: n = 78 women; PBO: n = 80 women). There were consistent and significant differential treatment effects (ODN-PBO) for total hip integral (5.4%), trabecular volumetric BMD (vBMD) (12.2%), and cortical vBMD (2.5%) at 24 months. There was no significant differential treatment effect on integral bone volume. Results for bone mineral content (BMC) closely matched those for vBMD for integral and trabecular compartments. However, with small but mostly significant differential increases in cortical volume (1.0% to 1.3%) and thickness (1.4% to 1.9%), the percentage cortical BMC increases were numerically larger than those of vBMD. With a total hip BMC differential treatment effect (ODN-PBO) of nearly 1000 mg, the proportions of BMC attributed to cortical gain were 45%, 44%, 52%, and 40% for the total, neck, trochanter, and intertrochanter subregions, respectively. In postmenopausal women treated for 2 years, odanacatib improved integral, trabecular, and cortical vBMD and BMC at all femur regions relative to placebo when assessed by MIAF. Cortical volume and thickness increased significantly in all regions except the femoral neck. The increase in cortical volume and BMC paralleled the increase in cortical vBMD, demonstrating a consistent effect of ODN on cortical bone. Approximately one-half of the absolute BMC gain occurred in cortical bone. © 2014 American Society for Bone and Mineral Research.
EVALuna2:10102